1977
DOI: 10.3382/ps.0561636
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Cholesterol Content of Araucana Chicken Eggs

Abstract: Comparative data collected over two years are presented which refute the popular press claims that blue-shelled eggs of Araucana chickens have higher protein levels and lower cholesterol levels than market eggs. These comparisons were made between the eggs from the strains of Araucanas and those of White Leghorns and Sex-links. None of the differences found between test groups in % protein/g. albumen and % protein/g. yolk were shown to be consistently related to any one test group type. However, all Araucana t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 3 publications
0
10
2
Order By: Relevance
“…In addition to its special ESC, the blue-shelled egg is popular in the market for another reason-the absence of trimethylaminuria resulting from the mutation of the flavin-containing monooxygenase 3 gene (Zhang, 2007). Previous studies showed that the Araucana egg has a larger yolk:albumen ratio, lower protein, and higher cholesterol content compared with commercial layers (Somes et al, 1977;Peterson et al, 1978). However, the productivity and egg quality of Dongxiang blue-shelled layers have not been systematically investigated.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to its special ESC, the blue-shelled egg is popular in the market for another reason-the absence of trimethylaminuria resulting from the mutation of the flavin-containing monooxygenase 3 gene (Zhang, 2007). Previous studies showed that the Araucana egg has a larger yolk:albumen ratio, lower protein, and higher cholesterol content compared with commercial layers (Somes et al, 1977;Peterson et al, 1978). However, the productivity and egg quality of Dongxiang blue-shelled layers have not been systematically investigated.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, there are other ESC, such as blue. Araucana is a well-known blue-shelled egg layer that has been very well documented (Somes et al, 1977;Peterson et al, 1978). A Chinese indigenous chicken breed named Dongxiang, which originated from Jiangxi Province, also lays blue-shelled eggs and has been used for commercial egg production recently.…”
Section: Introductionmentioning
confidence: 97%
“…As Somes et al (14)'s report it is probably the reason that Araucana had the highest yolk cholesterol might possibly be due to its lower egg production. It is also possible that layer straim have lower yolk cholesterol content because of the negative correlation between yolk cholesterol and egg production.…”
Section: Resultsmentioning
confidence: 88%
“…These results were similar to some previous reports. Edwards et al (5), Turk and Barnett (15), Somes et al (14), Ono and Inno (ll) have alsa reported that the differences among the chickcn strains for yolk cholesterol were statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative investigations on the quality traits of eggs and their cholesterol content have been performed during the second half of the 20 th century with the breed Araucana and commercial hybrids (13,14). Sadjadi et al (15) investigated the production traits and egg quality produced by F2 crosses between Araucana and Shaver Starcross "288", and found out lower egg production in crosses laying white eggs compared to those laying blue-green eggs, but no changes in egg quality.…”
Section: Introductionmentioning
confidence: 99%